2000
DOI: 10.1034/j.1600-0765.2000.035004194.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase type‐II is synthesized by human gingival tissue and cultured human gingival fibroblasts

Abstract: Nitric oxide is known to be an important inflammatory mediator, and is implicated in the pathophysiology of a range of inflammatory disorders. The aim of this study was to determine the localization and distribution of endothelial NOS (NOS-II) in human gingival tissue, and to ascertain if human gingival fibroblasts express NOS-II when stimulated with interferon gamma (IFN-gamma) and bacterial lipopolysaccharide (LPS). The distribution of NOS-II in inflamed and non-inflamed specimens of human gingivae was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 21 publications
1
78
2
7
Order By: Relevance
“…In the present study, NO production was measured indirectly using the level of nitrite in saliva, and an increase in salivary NO levels was observed in individuals with GCP. This result is similar to other studies that have shown increased levels of amino acids related to NO in periodontal disease (11), increased expression Table 1 Concentration of NO in saliva samples subjected to the Griess Reaction of iNOS in periodontal disease biopsy samples (25)(26)(27), as well as in gingival fibroblast cell cultures (12,28). In contrast, one report has described a reduction of salivary NO levels in individuals with adult periodontitis and with aggressive periodontitis (29).…”
Section: Discussioncontrasting
confidence: 34%
See 1 more Smart Citation
“…In the present study, NO production was measured indirectly using the level of nitrite in saliva, and an increase in salivary NO levels was observed in individuals with GCP. This result is similar to other studies that have shown increased levels of amino acids related to NO in periodontal disease (11), increased expression Table 1 Concentration of NO in saliva samples subjected to the Griess Reaction of iNOS in periodontal disease biopsy samples (25)(26)(27), as well as in gingival fibroblast cell cultures (12,28). In contrast, one report has described a reduction of salivary NO levels in individuals with adult periodontitis and with aggressive periodontitis (29).…”
Section: Discussioncontrasting
confidence: 34%
“…The NO released by this inducible NO synthase (iNOS) is generated for long periods by cells of the immune system among others. Cytokines and other bacterial products stimulate the expression of iNOS and interfere with periodontal disease progression (5,11,12). More specifically, bacterial lipopolysaccharide stimulates NO expression in bone, as well as in other tissues (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…These ROS are associated with the microvascular complications of diabetes. It is also known that severe periodontal disease can lead to endothelial dysfunction which is an early event in atherogenesis [15][16][17][18][19]. In this study, the compounding effect of coexisting diabetes and periodontitis on the levels of oxidative stress markers was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes may be considered best as a modifier of host-parasite interactions in the periodontium. [19,20] This modification may encourage the virulent expression of pathogens in the subgingival ecology in a direct fashion and/or an alteration of the host's inflammatory/immune response to these microorganisms. The net result is increased severity of periodontitis in subjects with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…NO synthesis and iNOS activity increase in inflamed periodontal tissues [20,[25][26][27][28] as a result of macrophage infiltration in periodontal tissues [29]. The literature includes only a few studies that evaluated iNOS activity in inflamed periodontal tissues.…”
Section: Introductionmentioning
confidence: 99%